On Orthogonal Generalized Derivations of Semiprime -Rings - Dey, Kalyan Kumar; Saha, Sanjay Kumar; Paul, Akhil Chandra (GANIT: Journal of Bangladesh Mathematical Society, 2019)
In this paper, we study the orthogonality of two generalized derivations in semiprime G-rings. Some results are obtained in connection with ideals of semiprime G-rings and using left annihilator which is taken to be zero. GANIT J. Bangladesh Math. Soc.Vol. 39 (2019) 63-70